Optimasi Derajat Grafting Stiren Akrilik pada Molekul Poli Isoprena Karet Alam untuk Pembuatan Cat Emulsi - Briliantina Rossa; Syelvia Putri Utami; Bahruddin Bahruddin (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2026)
Natural rubber modified through graft copolymerization offers improved compatibility and performance for water-based coating applications. This study investigates the optimization of grafting efficiency of styrene–acrylate onto natural rubber latex using a free-radical mechanism. Three processing variables—dry rubber content, styrene–acrylate concentration, and binder proportion—were evaluated using Central Composite Design within the Response Surface Methodology framework. The grafting process was carried out at 60 degrees Celsius for 210 minutes, followed by gravimetric analysis to determine the degree of grafting. Experimental results showed that dry rubber content exerted the most significant effect on grafting efficiency, while styrene–acrylate and binder levels contributed secondary but supportive influences. The response surface model demonstrated strong predictive capability, with an average prediction error of 2.84 percent. Optimal conditions were achieved at 60 percent dry rubber content, 10 percent styrene–acrylate, and approximately 19.7–20 percent binder, yielding a grafting degree of 63.32–64.11 percent in prediction and 64.23–67.21 percent in experimental validation. These findings confirm the effectiveness of controlled grafting to enhance polymer–monomer interactions and improve the performance of natural-rubber-based binders. The optimized grafted latex shows potential for industrial applications in waterborne coatings requiring strong adhesion, improved wash resistance, and stable film properties.